Perancangan Sistem Informasi Perpustakaan pada Sekolah Eka Wijaya Berbasis Java - Mirna Miranda; Puput Irfansyah; Erlando Doni Sirait (Jurnal Informatika Universitas Pamulang, 2021)
Libraries have books that are references or sources of knowledge that they want to know, sometimes even this information cannot be searched on the internet so that the number of books in the library is very large. With so many books in the library, of course, a system is needed to organize all the books so that these books can be recorded properly so as to reduce the risk of book census errors such as the number of books, borrowers, categories and also the delivery of more detailed information for books. because of that, it takes an information system design for a library. In designing an information system, a concept or research method is needed that can minimize mistakes in the flow of application creation, the method used is Waterfall modeling of this method, an application is made using Java Netbeans with MySQL database. By using this method, the application can run according to the flow, namely the details of the books in the library are in harmony with the actual situation and a decrease in data errors resulting in the loss of some information in the library such as the number of books, the number of borrowings, book details and so on. It makes it easier for users to find the information they want.